Interactive Effects of Aluminum and Cadmium on Phenolic Compounds, Antioxidant Enzyme Activity and Oxidative Stress in Blueberry (Vaccinium Corymbosum L.) Plantlets Cultivated in Vitro - Escudey-Castro, A; Escudey-Castro, A; Zuniga-Navarro, G; Manquian-Cerda, K; Manquian-Cerda, K (Academic Press, 2018)
To evaluate the potential role of phenolic compounds in Al and Cd stress tolerance mechanisms, Vaccinium corymbosum cv. Legacy plantlets were exposed to different metal concentrations. The present study used an in vitro plant model to test the effects of the following treatments: 100 μM Al; 100 μMAl + 50 μM Cd; and 100 μMAl + 100 μM Cd during periods of 7, 14, 21 and 30 days. The oxidative damage was determined by the accumulation of malondialdehyde (MDA) and hydrogen peroxide (H2O2). The antioxidant activity values were determined using 1,1-diphenyl-2-picrylhydrazine (DPPH) and the ferric reducing antioxidant power test (FRAP). Additionally, the phenolic compound concentrations were determined using HPLC-DAD. The exposure to Al and Cd increased the MDA and H2O2 contents differentially, while the antioxidant capacity values showed differences between DPPH and FRAP with the largest changes in FRAP relative to Cd. SOD had the highest activity in the first 7 days, leading to a significant increase in phenolic compounds observed after 14 days, and chlorogenic acid was the major compound identified. Our results revealed that phenolic compounds seem to play an important role in the response to ROS. Therefore, the mechanisms of tolerance to Al and Cd in V. corymbosum will be determined by the type of metal and time of exposure. © 2017 Elsevier Inc.